Rancang Bangun Sistem Pelaporan Bencana Berbasis Web dengan Metode Model View Controller di Kabupaten Ogan Komering Ilir - Rendi Febri Wardiansyah; Kurniawan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The Regional Disaster Management Agency (BPBD) of Ogan Komering Ilir Regency already hasa website but so far it has not been 100% complete. The disaster reporting input system from thecommunity is not yet available on the BPBD website of Ogan Komering Ilir Regency, so a website-based system is needed to facilitate reporting and publication of report results to the public as aform of accountability transparency. The purpose of this research is to design a web-baseddisaster reporting system using the Model View Controller method in Ogan Komering IlirRegency. The research was conducted at the Regional Disaster Management Agency (BPBD) ofOgan Komering Ilir Regency, South Sumatra Province, the application that will be developed isa web application with the PHP programming language and MySQL database with the Model-View-Controller (MVC) concept. Laravel version 9.* (latest as of August 2022), the webapplication will be distributed online via web hosting, the topic discussed in the web applicationis disaster reporting issues for the Ogan Komering Ilir Regency area, for disaster reporters whouse smartphone devices / Android tablet, the coordinates of the location of the complainant will be automatically recorded if GPS facilities are available on the Android device. A web applicationfor disaster reporting for the people of Ogan Komering Ilir Regency has been successfully createdand tested using the PHP programming language and MySQL database using the Model-View-Controller (MVC) concept by utilizing the latest Laravel framework, Laravel 9.*. The webapplication will be distributed online through web hosting with the domain name: bpbd-oki.id.